Mitotic slippage and the subsequent cell fates after inhibition of Aurora B during tubulin-binding agent–induced mitotic arrest. Issue 1 (December 2017) - Tsuda, Yasuo; Iimori, Makoto; Nakashima, Yuichiro; Nakanishi, Ryota; Ando, Koji; Ohgaki, Kippei; Kitao, Hiroyuki; Saeki, Hiroshi; Oki, Eiji; Maehara, Yoshihiko
Abstract Tubulin-binding agents (TBAs) are designed to target microtubule (MT) dynamics, resulting in compromised mitotic spindles and an unsatisfied spindle assembly checkpoint. The activity of Aurora B kinase is indispensable for TBA-induced mitotic arrest, and its inhibition causes mitotic slippage and postmitotic endoreduplication. However, the precise phenomenon underlying mitotic slippage, which is caused by treatment with both Aurora B inhibitors and TBAs, and the cell fate after postmitotic slippage are not completely understood. Here, we found that HeLa and breast cancer cells treated with the different types of TBAs, such as paclitaxel and eribulin (MT-stabilizing and MT-destabilizing agents, respectively), exhibited distinct behaviors of mitotic slippage on inhibition of Aurora B. In such conditions, the cell fates after postmitotic slippage vastly differed with respect to cell morphology, cell proliferation, and cytotoxicity in short-term culture; that is, the effects of inhibition of Aurora B were beneficial for cytotoxicity enhancement in eribulin treatment but not in paclitaxel. However, in long-term culture, the cells that survived after mitotic slippage underwent endoreduplication and became giant cells in both cases, resulting in cellular senescence. We propose that MT-destabilizing agents may be more appropriate than MT-stabilizing agents for treating cancer cells with a weakened Aurora B kinase activity.